1997
DOI: 10.1103/physrevb.56.15115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of valley-spin degeneracy on the screening of charged-impurity centers in two- and three-dimensional electronic devices

Abstract: Accurate characterization of charged impurity centers is of importance for the electronic devices and materials. The role of valley-spin degeneracy on the screening of an attractive ion by the mobile carriers is assessed within a range of systems from spin-polarized single-valley to six-valley. The screening is treated using the self-consistent local-field correction of Singwi and co-workers known as STLS. The bound electron wave function is formulated in the form of an integral equation. Friedel oscillations … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…17. The method was later applied to charge impurities by Bulutay et al 18 The calculations of Ref. 15 were performed for Յ 6, too few flavors to gauge the applicability of the analytic many-flavor approximation, which is estimated to apply at around six or more flavors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17. The method was later applied to charge impurities by Bulutay et al 18 The calculations of Ref. 15 were performed for Յ 6, too few flavors to gauge the applicability of the analytic many-flavor approximation, which is estimated to apply at around six or more flavors.…”
Section: Introductionmentioning
confidence: 99%
“…[17]. The method was later applied to charge impurities by Bulutay et al [18]. The calculations of Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of the binding energy of a hydrogenic impurity due to electron screening was studied extensively in the past [1][2][3][4][5][6][7][8][9]. Such calculations are important for impure metals and doped semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…The binding energy was calculated by using different approximations for the screening function. The effect of screening by an electron gas on a single charged impurity in three dimensions (3D) [1][2][3][4][5][6] and in two dimensions (2D) [5][6][7][8][9] was considered. In 3D it was found that the binding energy of a positively charged impurity vanishes if the screening density of electrons is larger than a critical density, the Mott density.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of the valley degeneracy on the bound-state energy of screened impurities has recently been discussed for the two-and three-dimensional electron gas using the test-charge±test-charge interaction [12]. A detailed discussion of the differences between the test-charge±test-charge interaction potential and the test-charge±electron interaction potential was given before [6,7,9].…”
mentioning
confidence: 99%